Clinical characteristics and prognosis of pulmonary inflammatory myofibroblastic tumor: An over 10‐year retrospective analysis - Na Zhang; Qi Zeng; Chenghao Chen; Jie Yu; Dong Yan; Changqi Xu; Dingyi Liu; Qian Zhang; Xu Zhang (Wiley, 2020)
Abstract Importance Pulmonary inflammatory myofibroblastic tumors (PIMTs) are primary lung tumors in children. Misdiagnosis easily occurs because of the nonspecific clinical manifestations, laboratory examination results, and imaging findings in affected patients. Objective To summarize the clinical characteristics, diagnosis, and prognosis of children with PIMTs. Methods This retrospective analysis included 23 children with PIMTs who received treatment in our hospital from January 2008 to January 2019. The clinical manifestations, laboratory examination results, and computed tomography findings were retrospectively analyzed. Results The population included 13 boys and 10 girls, with a median age at onset of 78 months (range, 10-126 months). Fourteen patients had PIMT lesions in the right lung and nine patients had PIMT lesions in the left lung. The surgical procedures included pulmonary wedge resection, pulmonary lobectomy, and total pneumonectomy. The median operation time was 115 min (range, 45-235 min); the median intraoperative blood loss volume was 30 mL (range, 3-500 mL). During the operation, one patient each had pulmonary hemorrhage, vena cava hemorrhage, and thoracic duct injury. Postoperative complications included pulmonary embolism in one patient and tumor recurrence in two patients; neither of these complications recurred after reoperation. The median follow‐up period was 49 months (range, 2-127 months). Interpretation Children with PIMTs exhibited good prognoses and primarily underwent surgical resection as treatment. Complete preoperative evaluation should be performed in affected patients.